STRATEGI KOMUNIKASI POLITIK PENGGUNAAN BALIHO VERSUS MEDIA SOSIAL OLEH PARTAI DEMOKRASI INDONESIA PERJUANGAN TAHUN 2021 - Rizki Amalia Yanuartha; Royke R. Siahainenia; Putri Hergianasari; Kurniawan Netanyahu (Administraus, 2022)
This paper discusses the political communication strategy used by two political figures from the 2021 Indonesian Democratic Party of Struggle, Puan Maharani and Ganjar Pranowo. This study describes the political communication strategy of using billboards by Puan Maharani's support group and social media by Friends of Ganjar Pranowo. The benefit of this research is not only to provide the latest information or knowledge in social science studies but also to be a new point of view that comes from efforts to explore political communication in carrying Indonesian presidential candidates to compete in the 2024 presidential and vice-presidential elections. 2022 to 2024 will be a political year where the Covid-19 pandemic is still hitting Indonesia. The use of every media, be it conventional media or new media in the 5.0 era, became the main point in achieving the goals of political communication for each political party figure or cadre. Each existing media has its own strengths and weaknesses. The right political strategy and message will determine the achievement of political communication.